Prevalencia de vermes pulmonares en las especies bovina, equina, ovina y porcina en el alto del Sinú - Espitia Espitia, José María; Jiménez Rodríguez, Joaquín Eduardo; Pacheco Montes, Augusto Antonio (Universidad de Córdoba - UNICORDOBA, 2018)
Ganadería bovina